2010
DOI: 10.1051/ebr/2010009
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating biological containment strategies for pollen-mediated gene flow

Abstract: Several biological containment methods have been developed to reduce pollen dispersal; many of them only have a proof of concept in a model plant species. This review focuses on biological containment measures which were tested for their long-term efficiency at the greenhouse or field scale level, i.e. plastid transformation, transgene excission, cleistogamy and cytoplasmic male sterility (CMS). Pollen-mediated gene transfer in transplastomic tobacco could occur at very low frequencies if the predominant mode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…In crop species (e.g. wheat, barley, rice), cleistogamic breeding systems may have been selected during domestication to limit gene flow and preserve preferred gene combinations [229][230][231][232][233]. The absence of pollen presentation in cleistogamic self-pollinating plants is thought to be a protection against abiotic stresses such as drought and heat, as pollen number is considered less of a constraint for pollination in cleistogamic compared to chasmogamic species [227,234].…”
Section: Recalcitrant Pollen and Self-pollinationmentioning
confidence: 99%
“…In crop species (e.g. wheat, barley, rice), cleistogamic breeding systems may have been selected during domestication to limit gene flow and preserve preferred gene combinations [229][230][231][232][233]. The absence of pollen presentation in cleistogamic self-pollinating plants is thought to be a protection against abiotic stresses such as drought and heat, as pollen number is considered less of a constraint for pollination in cleistogamic compared to chasmogamic species [227,234].…”
Section: Recalcitrant Pollen and Self-pollinationmentioning
confidence: 99%
“…[2][11]. Although a steady progress has been achieved in recent decades, Hüsken et al (2010) concluded that no single containment strategy would result in 100% reduction of gene flow, suggesting that combinations of complementary containment systems are required [12].…”
Section: Introductionmentioning
confidence: 99%
“…Although several biocontainment methods have been developed to reduce transgenic pollen dispersal, they have been tested mainly in model plants [11]. Among these methods, site-specific recombination is recognized as a promising strategy for transgene removal and other manipulations of the plant genome [12].…”
Section: Introductionmentioning
confidence: 99%